2021
DOI: 10.1080/09500693.2021.1902015
|View full text |Cite
|
Sign up to set email alerts
|

Doing science through translanguaging: a study of translanguaging practices in secondary English as a medium of instruction science laboratory sessions

Abstract: This study explores how students in a joint process of knowledge construction through the use of multilingual and multimodal resources in groups promotes the learning of scientific concepts in the context of laboratory work. Inductive qualitative discourse analysis was conducted to examine how students' translanguage in a group completing tasks in two Grade 10 secondary science labs (biology and chemistry) in a Hong Kong EMI secondary school and how such a joint process of knowledge construction promotes the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…Firstly, the study was contextualized in an EMI finance course at an international school on the Chinese mainland, where little relevant empirical evidence has hitherto been produced. Previous research has tended to focus on classrooms where a more multilingual tradition prevails, or where English used to be, or still is, one of the official languages [32,44,45,48]. Nevertheless, although English is the designated campus language for almost all international schools in the metropolitan Shanghai area, these schools also function as ideal environments for interlocutors to incorporate various linguistic resources and engage in meaningful multilingual conversations to enhance content learning and improve biliteracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the study was contextualized in an EMI finance course at an international school on the Chinese mainland, where little relevant empirical evidence has hitherto been produced. Previous research has tended to focus on classrooms where a more multilingual tradition prevails, or where English used to be, or still is, one of the official languages [32,44,45,48]. Nevertheless, although English is the designated campus language for almost all international schools in the metropolitan Shanghai area, these schools also function as ideal environments for interlocutors to incorporate various linguistic resources and engage in meaningful multilingual conversations to enhance content learning and improve biliteracy.…”
Section: Discussionmentioning
confidence: 99%
“…These classrooms usually follow an agenda of bilingual teaching and learning and consider academic language acquisition to be as important as content learning [42,43]. A brief review of recent literature reveals that secondary science classrooms appear to be the most frequently selected setting for translanguaging studies in EMI contexts [44,45]. For instance, Tai and Li [46] discovered that translanguaging can be used to create a playful, informal atmosphere in EMI science classrooms in order to facilitate communication and content learning as well as promote interpersonal relationships.…”
Section: Pedagogical Translanguaging In Emi Classroomsmentioning
confidence: 99%
“…For instance, translanguaging was found to be a favourable approach for conducting science (biology and chemistry) laboratory sessions. Translanguaging is defined as "the exploitation of multiple languages and semiotic resources in a multilingual repertoire", which, in this case, helped to facilitate students' joint process of knowledge construction and promote their acquisition of scientific concepts [50] (p. 2). It may well be the case, then, that EMI policy for STEM subjects could be taken up and implemented differently not just in individual teacher-student interactions but also in different subject fields.…”
Section: Cantonese (L1) In the Classroommentioning
confidence: 99%
“…Since this initial conceptualisation, translanguaging has come to encompass multiple meaning-making resources and not just verbal language (see [58]). Indeed, recent research has shown how this process of moving between multiple semiotic resources can increase the amount of dialogue, understanding, and even enjoyment in science classrooms (e.g., [50]). This has been especially true in Chinese contexts (see [59][60][61]).…”
Section: Translanguaging As An Enabler Of Science-teaching Activitiesmentioning
confidence: 99%
See 1 more Smart Citation